Comparative analysis of pulmonary function impairment in adolescent idiopathic vs. congenital scoliosis - Bashir, Khurram; Sabir, Nadeem; Rehman, Zia-Ur-; Aziz, M. Omar; Awan, Malik Ahsan Atta; Dogar, Ammar; Nadeem, Umair; Aziz, Amer (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Scoliosis is the main three-dimensional pathological backbone deformation with direct effects on the thoracic cage and a prevalence of 0.3 to 15.3% of the population. Aim: To assess the comparison of pulmonary function impairment in adolescent idiopathic and congenital scoliosis. Place and duration of study: Department of Orthopedic & Spine Center, Ghurki Trust Teaching Hospital Lahore from 1st January 2020 to 31st August 2020. Methodology: In this cross-sectional study 30 patients diagnosed with Idiopathic congenital scoliosis after the approval from the Ethical Committee of the hospital (15 idiopathic and 15 congenital scoliosis) were enrolled. The data were collected using predesigned proforma, including demographics (gender, age, BMI, Cobb’s angle, and side of deviation) and outcome variables to measure pulmonary function impairment. In all patients, pulmonary function tests were performed. Results: In group A, the mean value of FVC (%) was lower than 80% of the predicted normal value as 59.8±12.0 as compared to group B 78.32±21.35%. The average predicted value of FEV1 was 62.3±13.5%slightly decreased in group A (below 80% of the predicted normal value) compared to group B81.47±19.88%. The FEV1/FVC ratio was normal in both groups (>70% predicted). The result also revealed a significant difference in both groups as (p-value<0.05). Conclusion: Idiopathic and congenital scoliosis is a common thoracic cage weakening deformity with potentially significant and permanent effects of the lungs. As pulmonary symptoms may become clinically apparent unless major and permanent changes have taken place in lung function. It is advisable to recognise the issue early and to conduct routine pulmonary function tests.